Display Unit for Bangla Characters - Rahman, Mohammad Osiur; Khan, Mohammad Aktaruzzaman (IIUC Studies, 2009)
Segmented representation is used in lieu of the dot matrices representation for alphanumeric characters of different languages. Due to concerns of cost, power loss and design complexity, the segmented representation becomes more popular over the dot matrices. There are very limited display units for English, Arabic, and Bangla alphanumeric characters. 18-segments display is normally used to display the entire alphabetic character of English. But there is no standard display unit for Bangla Alphabetic Characters. Although recently different segmented display models for Bangla characters have been proposed, the quality of the characters stay below the mark. In this paper, 26-segments display for Bangla alphabetic character has been proposed. From the review it appears that it is the first proposed display in the world for Bangla Alphabetic Character. Here a grid structure consisting of 26 segments has been discovered. All Bangla characters vowel and consonants can be characterized by using this grid structure. As there can be at least vowels (12), consonants (39), punctuation, and some other symbols to be displayed, 6-bit inputs are used to represent each character. After analyzing which segments will be activated for which character, appropriate logic function and circuits have been derived in order to display each Bangla character. Finally, a comparative analysis is made among the different proposed segmented display models to find out the cost and effectiveness in terms of display quality, power loss, and design complexity. Keywords: 7-segment, 12-segment, 17-segment, 18- segment, non-overlapping segments, K-map. doi: 10.3329/iiucs.v4i0.2855 IIUC STUDIES Vol. - 4, December 2007 (p 71-86)